Cut, don’t cut - moving the viewer through a story in animated VR - Hodgkinson, Gray (2020)
One of the most disruptive and disorienting experiences in VR is the camera cut, when the entire 360-degree panoramic view undergoes a total change from one view to another. While a ubiquitous device in 2D media, the camera cut has a dramatically stronger efect in VR. In the VR world, the screen is all encompassing, so any interruption to this view is fully disruptive. Furthermore, the viewer may have no fxed visual references, so any sudden changes will likely cause physical disorientation. In VR, a camera cut is like a blink, and upon opening the eyes, the viewer has been instantly transported to another location. Changes in camera position, angle, orientation, lighting, and any aspect of point of view will have an immediate, unconscious visceral efect on the viewer. Deliberate cinematic devices such as cuts and other transition devices such as teleportation, also have the risk of decreasing the sense of immersion, and consequently, presence. The VR experience has been seen by many to ofer an increased state of presence, and consequently, an increase in empathy that 2D cannot achieve, but these qualities seem to contradict the narrative tools of direction and editing. However, creators of animated VR narratives are fnding their own solutions that retain the power of storytelling while beneftting from the experiential qualities of VR.